Parameters estimation of the drying process of industrial ceramic bricks via concentrated analysis model (Research, Society and Development, 2021)
The manufacture of ceramic materials, as an industrial activity, was due to the growth of large civil constructions. The manufacture of these materials comprises the stages of extraction, processing, homogenization, conformation, drying and firing. Drying is a thermodynamic process that precedes firing, in which, due to the supply of thermal energy, the water that was added to the solid during its formation evaporated. It’s a process that involves complex phenomena of heat and mass transfer and, therefore, requires the generation of mathematical models that describe the process with great physical realism. The existence of mathematical models occurs, above all, with the aim of describing certain phenomena, seeking to understand and solve irregularities that exist during the process. Parameter estimation is a technique that makes it possible to obtain process control variables and accurately describe the drying phenomenon. In this context, the present study aimed, through mathematical modeling and numerical simulation, to analyze the thermal and gravimetric behavior of industrial ceramic bricks during the drying process and to estimate the process parameters. For this, mathematical models based on the concentrated analysis method were proposed and adjusted to experimental data obtained in the literature, via Statistica® software. Results regarding the behavior of ceramic bricks during the drying process were exposed and analyzed. It was possible to conclude that the proposed mathematical model adequately adjusted to the collected experimental data, with a coefficient of determination greater than 0.9 and that, through parameter estimation, it was possible to define the process control variables and obtain the convective transfer coefficients of heat and mass.